2004
DOI: 10.1016/s0014-5793(04)00034-1
|View full text |Cite
|
Sign up to set email alerts
|

Apg‐2 has a chaperone‐like activity similar to Hsp110 and is overexpressed in hepatocellular carcinomas

Abstract: Hepatocellular carcinoma (HCC) is the ¢fth most common cancer in the world. We constructed subtracted cDNA libraries enriched with genes overexpressed in HCCs. Among the 17 genes identi¢ed were molecular chaperones, Hsp110, Hsp90B, and Hsp70-1. Expression of the Hsp110 family members was further analyzed, and increased transcript levels of Hsp110 and Apg-2, but not Apg-1, were found in 12 and 14, respectively, of 18 HCCs. Immunohistochemical analysis demonstrated the overexpression of the proteins in tumor cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 34 publications
2
33
0
Order By: Relevance
“…Moreover, overexpression of Apg-2 conferred a proliferative advantage to BaF3-BCR/ABL cells in vitro. In accord with our findings, a previous study has demonstrated that Apg-2 is overexpressed in hepatocellular carcinoma (16). Together, these findings suggested that Apg-2 is overexpressed when exposed to H 2 O 2 in BaF3-BCR/ABL cells, which promotes cell proliferation.…”
Section: Baf3-bcr/abl Cells With Apg-2 Overexpression Had Higher Propsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, overexpression of Apg-2 conferred a proliferative advantage to BaF3-BCR/ABL cells in vitro. In accord with our findings, a previous study has demonstrated that Apg-2 is overexpressed in hepatocellular carcinoma (16). Together, these findings suggested that Apg-2 is overexpressed when exposed to H 2 O 2 in BaF3-BCR/ABL cells, which promotes cell proliferation.…”
Section: Baf3-bcr/abl Cells With Apg-2 Overexpression Had Higher Propsupporting
confidence: 92%
“…Interestingly, Apg-2 protein shows a chaperone-like activity similar to Hsp110 and is overexpressed in hepatocellular carcinomas (16) as well as in pancreatic cancer (17), indicating that Apg-2 may be critical to tumor progression. In our previous comparative proteomics study, we found that Apg-2 was overexpressed in BaF3-BCR/ABL cells that were treated with hydrogen peroxide (H 2 O 2 ) comparing to BaF3-MIGR1 cells (unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…By constructing subtracted cDNA libraries, we have previously identified 19 genes overexpressed in HCCs, including two novel genes (18,19). One of these genes was named HSCO (hepatoma subtracted-cDNA library clone one) (20).…”
mentioning
confidence: 99%
“…Similarly, several junctional scaffolding proteins are bound and inactivated by viral oncogenes (Glaunsinger et al, 2001;Latorre et al, 2005). By contrast, ZONAB and its activating protein Apg2 are both upregulated in hepatocellular carcinomas, which suggests that this proliferationpromoting pathway is stimulated (Arakawa et al, 2004;Gotoh et al, 2004;Hayashi et al, 2002).…”
Section: Tjs In Diseasementioning
confidence: 99%